Performance of Three Tropical Plant Species as Phytoremediators for Selected Heavy Metals in Sewage Sludge - Ghafoor, Mayram (2011)
Heavy metal contamination is one of the most pressing threats to water and soil resources as well as human health. Unlike organic compounds, metals cannot be degraded. Most of the conventional remedial technologies are expensive and also cause negative impact on the environment. Phytoremediation is a cost effective, environmental friendly and aesthetically pleasing approach most suitable to remediate metal-contaminated soils. This study was to 1) determine the concentrations of Cu, Pb and Zn in different plant parts (stem, leaf, root) growing on soils contaminated with sewage sludge and 2) evaluate the potential of the three different tropical species as phytoremediators for Cu, Pb and Zn in sewage sludge on the basis of BCF and TF. Three plant species namely Jatropha curcas L., Acacia mangium Willd. and Hopea odorata Roxb. were used to investigate the phytoextraction efficiency for Cu, Pb and Zn. The experiment was laid out a Randomizad Complete Block Design (RCBD) with four replications and was conducted in a green house. The growth medium was sewage sludge biosolid applied at six different levels in the following ratios of soil to sludge: 100% soil (control), 80:20, 60:40, 40:60, 20:80 and 100% sludge. Cu, Pb and Zn concentrations in the growth medium and plants were analyzed by EPA Method 3051 using Inductively Coupled Plasma-Optical Emission Spectrometer (ICP/OES). Results showed that total concentrations of Cu, Pb and Zn in the growth medium before planting were in the range of 13.67 mg kg-1 to 122.13 mg kg-1, 6.18 mg kg-1 to 69.87 mg kg-1 and 43.51 mg kg-1 to 1206 mg kg-1, respectively. Cu absorption was in the range of 0.5 to 11.62 mg kg-1 for Jatropha curcas, 0.3 to 6.62 mg kg-1 in Acacia mangium and 0.4 to 11.52 mg kg-1 for Hopea odorata. Pb absorption was in the range of 0.3 to 141.6 mg kg-1 for Jatropha curcas, 0.15 to 102.7 mg kg-1 in Acacia mangium and 0.25 to 123.2 mg kg-1 in Hopea odorata. Zn absorption was in the range of 12.4 to 1617 mg kg-1for Jatropha curcas, 6.6 to 1435 mg kg-1 in Acacia mangium and 26.07 to 438.4 mg kg-1 for Hopea odorata. In all the species, the concentrations of Cu, Pb and Zn were significantly (P ≤ 0.05) different among the different levels of biosolids and different plant parts. For Cu, values of bioconcentration factor (BCF) and translocation factor (TF) for all three species were less than one which indicates that they are not suitable for phytoextraction of Cu. In Jatropha curcas TF and BCF values ranged from 0.34 to 0.87 and 0.09 to 0.26, respectively. For Acacia mangium TF was in the range of 0.24 to 0.99 and BCF was in the range of 0.05 to 0.24. In Hopea odorata TF and BCF values ranged from 0.72 to 0.98 and 0.09 to 0.19, respectively. For Pb, BCF values were more than one and TF values were less than one for all three species which indicates that they are not suitable for phytoextraction of Pb. In Jatropha curcas TF and BCF values ranged from 0.06 to 0.09 and 2.02 to 6.80, respectively. For Acacia mangium TF was in the range of 0.02 to 0.06 and BCF was in the range of 1.46 to 4.02. In Hopea odorata TF and BCF, values ranged from 0.01 to 0.04 and 1.76 to 8.98, respectively. In the case of Zn, values of bioconcentration factor (BCF) and translocation factor (TF) for Acacia mangium were more than 1. The highest BCF value for this species was 1.33 and the highest TF value was 1.93 which indicates that Acacia mangium is suitable for phytoextraction. In Jatropha curcas BCF values were more than one and also the highest at 3.13 but TF values were less than one indicating that this species is not suitable for phytoextraction of Zn. Both BCF and TF values in Hopea odorata were less than one which indicates that this species is not an effective phytoextractor of Zn contaminated soil. This study showed that Malaysian sewage sludge contains high amounts of heavy metals particularly Cu, Pb and Zn and it has to be remediated before using it as a fertilizer. Among the three heavy metals, Zn was present in the highest concentration in the sludge. Between the three plant species tested for this research, Acacia mangium showed the ability of phytoextraction for Zn. In order to confirm the results of this study a field experiment should be conducted.